Letter from the Editor (International Journal of First Aid Education)
Covers the ways this issue aims to foster critical dialogue for the benefit of societal improvement, from the series of letters debating the use of superglue in first aid kits, a conference the IJFAE co-sponsored, and the addition of new manuscript types like conference abstracts to encourage more submissions.